2020
DOI: 10.1002/pds.4955
|View full text |Cite
|
Sign up to set email alerts
|

Impact of EMA regulatory label changes on systemic diclofenac initiation, discontinuation, and switching to other pain medicines in Scotland, England, Denmark, and The Netherlands

Abstract: Purpose In June 2013 a European Medicines Agency referral procedure concluded that diclofenac was associated with an elevated risk of acute cardiovascular events and contraindications, warnings, and changes to the product information were implemented across the European Union. This study measured the impact of the regulatory action on the prescribing of systemic diclofenac in Denmark, The Netherlands, England, and Scotland. Methods Quarterly time series analyses measuring diclofenac prescription initiation, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
16
2
Order By: Relevance
“…This would be in keeping with the findings from a systematic review examining the impact of United States risk advisories, which suggested such advisories were more effective at decreasing initiation of targeted medicines and less effective at bringing about their discontinuation 2 . This has also been seen with another recent European study 20 . While the immediate rise in hydroxyzine discontinuation in England is considered an intended effect, it is uncertain why hydroxyzine discontinuation should have fallen in Denmark particularly when the rate of hydroxyzine initiation did not change.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This would be in keeping with the findings from a systematic review examining the impact of United States risk advisories, which suggested such advisories were more effective at decreasing initiation of targeted medicines and less effective at bringing about their discontinuation 2 . This has also been seen with another recent European study 20 . While the immediate rise in hydroxyzine discontinuation in England is considered an intended effect, it is uncertain why hydroxyzine discontinuation should have fallen in Denmark particularly when the rate of hydroxyzine initiation did not change.…”
Section: Discussionsupporting
confidence: 74%
“…However, other downstream factors may also have influenced this process and therefore we used the quarter when the referral concluded as our intervention time point when information first became public. Nevertheless, we add to the evidence demonstrating geographical variation in the impact of pharmacovigilance decisions can occur despite being subject to the same recommendations 3,20‐25 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the role of regulatory agencies is to alert prescribers to new safety information, the impact of such decisions on healthcare behaviour and health outcomes is challenging to measure and often poorly understood, with previous studies using heterogeneous and poor quality methods of evaluation 12–14 . We recently examined the impact of the 2013 EMA intervention on overall diclofenac prescribing, discontinuation and switching to alternative medicines in the general population 15 . We now report the impact of the 2013 EMA risk minimisation measures for diclofenac among patients specifically targeted by the intervention, namely among those with or at high risk of cardiovascular disease, across several EU countries to determine to what extent impact may have varied.…”
Section: Introductionmentioning
confidence: 99%